New International Calibration Standard (ICE-3) for HPLC Analysis of α-and β-acids: Submitted on behalf of the International Hop Standards Committee - Biendl, Martin (BrewingScience, 2010)
The International Hop Standards Committee (IHSC), announces the release of a new calibration standard, ICE-3, for the HPLC analysis of α- and β-acids. This standard replaces ICE-2, which is now withdrawn.